(untitled) - Hayt, William Hart (Boston, MA., 2007)
The hallmark feature of this classic text is its focus on the student – it is written so that students may teach the science of circuit analysis to themselves. Terms are clearly defined when they are introduced, basic material appears toward the beginning of each chapter and is explained carefully and in detail, and numerical examples are used to introduce and suggest general results. Simple practice problems appear throughout each chapter, while more difficult problems appear at the ends of chapters, following the order of presentation of text material. This introduction and resulting repetition provide an important boost to the learning process. Hayt's rich pedagogy supports and encourages the student throughout by offering tips and warnings, using design to highlight key material, and providing lots of opportunities for hands-on learning. The thorough exposition of topics is delivered in an informal way that underscores the authors’ conviction that circuit analysis can and should be fun.
Keywords: Electric circuit analysis,Electric network analysis